Investigation of energy and mass balance “Trimyx-3M” Galatea multipole magnetic trap - Bishaev, A.M.; Bugrova, A.I.; Kozintseva, M.V.; Lipatov, A.S.; Savelyev, V.V.; Sigov, A.S.; Tarelkin, I.A.; Terekhov, V.A.; Desyatskov, A.V. (Вопросы атомной науки и техники, 2011)
In the work using Rogowski loop, measurements of the diamagnetic current, generating in the plasma volume of the
“Trimyx-3M” Galatea multipole magnetic trap under its filling by plasmoids have been carried out. These
measurements are confirmed by signals from diamagnetic probes. The mean value of the energy in plasma volume in
the process of the trap filling by plasma and during plasma decay have been determined by the magnitude of
diamagnetic current. These measurements are carried out simultaneously with the measurement of the time dependence
of mean plasma density by microwave interferometer. За допомогою поясу Роговського здійснено виміри діамагнітного струму, що виникає в плазмовому об’ємі мультипольної магнітної пастки-Галатеї "Трімікс-3М" при наповненні її плазмовими згустками. Ці виміри підтверджені сигналами з діамагнітних зондів. За величиною діамагнітного струму визначалася величина енергії в плазмовому об’ємі і її зміна в процесі заповнення пастки плазмою і її розпаду. Виміри проведено одночасно з вимірами за допомогою СВЧ-інтерферометра часової залежності середньої концентрації плазми. С помощью пояса Роговского произведены измерения диамагнитного тока, возникающего в плазменном объеме мультипольной магнитной ловушки-Галатеи «Тримикс-3М» при наполнении ее плазменными сгустками. Эти измерения подтверждены сигналами с диамагнитных зондов. По величине диамагнитного тока определялась величина энергии в плазменном объеме и ее изменение в процессе заполнения ловушки плазмой и её распада. Измерения проведены одновременно с измерением с помощью СВЧ-интерферометра временной зависимости средней концентрации плазмы.